Mortality After Cryptococcal Infection in the Modern Antiretroviral Therapy Era. (1st September 2019) - Hevey, Matthew A.; Presti, Rachel M.; O'Halloran, Jane A.; Larson, Lindsey; Raval, Krunal; Powderly, William G.; Spec, Andrej
Abstract : Background: The prevalence of cryptococcosis in people living with HIV (PLWH) in the developed world has decreased considerably in the modern antiretroviral therapy (ART) era. Although early mortality of PLWH with opportunistic infections is well understood, overall mortality has not been previously evaluated. Methods: We conducted a retrospective cohort study of cryptococcosis in PLWH from January 1, 2002, to July 1, 2017. Data were also evaluated before and after 2008 to evaluate the possible effect of modern ART on outcomes. Death date was obtained from the hospital's medical informatics database and the Social Security Death Index. Participants were grouped as survivors, early-mortality (death <90 days), and late-mortality (death ≥90 days) individuals. Results: We reviewed 105 PLWH with cryptococcosis, with 55 survivors (52.4%), 17 early-mortality (16.2%), and 33 late-mortality individuals (31.4%). Overall, mortality was 47.6% (n = 50) with a median follow-up of 3.7 years (interquartile range 1.1, 8.1 years). Late-mortality individuals were less likely to be virally suppressed at the last observation compared with survivors (24% vs 62%, P < 0.001). Individuals diagnosed in the modern ART era had significantly lower mortality (hazard ratio 0.5, confidence interval: 0.2 to 0.8) and were more likely to be virally suppressed at the last observation (57% vs 29%, P = 0.003). Individuals with government-provided insurance had a higher mortality compared to those with private insurance (hazard ratio 2.8, confidence interval: 1.1 to 7.2, P = 0.013). Conclusions: Despite improvements in ART, PLWH have high mortality after cryptococcal infection that persists beyond their initial hospitalization. Lower mortality was associated with increased HIV viral suppression and private insurance in the modern ART era. Abstract : Supplemental Digital Content is Available in the Text.